Imagem corporal e saúde mental de mulheres que sofreram violência doméstica: diferenciais segundo raça/cor da pele. - Jesus, Luane Sales de (2015)
The body image involves a tangle of factors that define how individuals see themselves and how they think and are seen by others people. Be satisfied or not with de image body is a constant training process, as from the experiences, the individual may feeling dissatisfied with your body image. The violence and racial discrimination are listed how negative influencers for the concept of body image of the individual, because after suffered aggresions by subject, is possible that your concept of satisfaction with your bodyimage, be reversed for dissatisfaction. However, there aren´t studies in Literature the relate to mental health and feelings of women`s satisfaction/dissatisfaction feelings, victms of domestic violence with their body image, considering the differentials by race/color. OBJECTIVE: Avaliate the satisfaction with body image and situation of mental health of the women, victms of domestic violence highlighting differences by race/color, attended at Women´s Reference Center in Bahia. METHODOLOGY: A descriptive quantitative study used document analysis and interviews among the women attended at women´s Reference Dandara Center, in Serrinha-Bahia. An individual questionnaire was applied, with the Stunkard Silhouettes Scale, the Self Report Questionnaire (SRQ-20), Beck´s depression inventory and the Patient Health Questionnaire (PHQ). The data collection was searched in October 2014 to June 2015. RESULTS: The most women were young, single, with children, low level of education, took head family, worked,they received less than a minimum salary, practiced leisure activities and were predominantly black women, also as related most variables from race/color. There was a predominance of the violence by intimate partners, into their own homes, specially the psychological and physical violence. Found predominance of dissatisfaction about their body image, particularly about black women, aged less than 40 years, without partners and received less than a minimum salary. The most women, indicated like dissatisfied about body image, showed high levels of disorders and depression. CONCLUSION: Leave the this violent means and the reduction of racial discriminations, can be important actions to reduce the dissatisfactions about the body image, mental disorders and depression. This study provides informations to developing strategies for a good mental health of the women in domestic violence situation, specially the black women, to minimize the consequences of suffered violence by them.